Processes of the state police: subjective impact on young people from Córdoba in the popular sectors (Dissertare, 2023)
The article aims to analyze the subjective effects of police processes in relation to young people from the popular sectors of Córdoba, Argentina. To this end, the configuration of criminal selectivity scenarios and the abusive use of police force is analyzed from the youth perspective. Using a psychosocial approach, we attempt to reconstruct the subjective marks that police force imposes, exploring the symbolic and emotional meanings that young people construct around their experiences with the police. This article is the result of a research process that lasted eight years, in which we worked with young girls from Córdoba mobilized against police violence. A qualitative methodology was applied, supported by in-depth interviews with young people between 16 and 34 years old from the city of Córdoba. The findings suggest that policing processes shape the subjective constitution of these young women, conditioned by experiences of undervaluation and rejection. We notice the production of an emotionality linked to feelings of helplessness and shame, in line with a problem of self and hetero social recognition, reinforcing the precariousness of the youth and popular condition.
Keywords: policing processes; police harassment; subjectivity; youth